Digestive disorders and Intestinal microbiota - Nouvenne, Antonio; Ticinesi, Andrea; Tana, Claudio; Prati, Beatrice; Catania, Pamela; Miraglia, Chiara; de' Angelis, Gian Luigi; Di Mario, Francesco; Meschi, Tiziana (Acta Biomedica Atenei Parmensis, 2018)
In the last decade, a barge body of scientific literature has suggested that specific alterations of the gut microbiota may be associated with ther development and clinical course of several gastrointestinal diseases, including irritable bowel syndrome, inflammatory bowel disease, celiac disease, gastrointestinal cancer and Clostridium difficile infection. These alterations are often referred to as “dysbiosis”, a generic term designing reduction of gut microbiota biodiversity and alterations in its composition. Here, we provide a synthetic overview of the key concepts on the relationship between intestinal microbiota and gastrointestinal diseases, focusing on the translation of these concepts into clinical practice.